Analisis Kreativitas Guru dalam Pembelajaran dengan Kurikulum Merdeka di TK Pelangi Kasih - Harminanti, A. Tuty; Sumarno, Sumarno; Dwijayanti, Ida (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
Increasing teacher creativity in learning with an independent curriculum is the aim of this research. The independent curriculum is a child-centered curriculum. The independent curriculum aims to restore learning from teacher-centered to child-centered learning, so that learning matches the child's interests and talents. Creativity is one of the teacher's skills that must be developed and improved because it is related to improving the quality of education. Efforts to increase creativity are based on five creativity guidelines, namely: Fluency, Flexibility, Originality, Elaboration, Redefinition. The data collection process used interviews with teachers by providing interview instruments which were given to 2 teachers via WhatsApp. The results of the interview show that teacher creativity in stimulating children to develop creativity is very necessary, for this reason teachers need to increase creativity through training activities, workshops, seminars on creativity, so that teachers are expected to be able to bring out the creativity that students have.